Modern control systems - Dorf, Richard C.; Bishop, Robert H. (Harlow, United Kingdom : Pearson Education Limited, 2022)
The role of control systems in green engineering will continue to expand as the global issues facing us require ever increasing levels of automation and precision. In the book, we present key examples from green engineering such as wind turbine control and modeling of a photovoltaic generator for feedback control to achieve maximum power delivery as the sunlight varies over time.
1. Introduction to Control Systems -- 2. Mathematical Models of Systems -- 3. State Variable Models -- 4. Feedback Control System Characteristics -- 5. The Performance of Feedback Control Systems -- 6. The Stability of Linear Feedback Systems -- 7. The Root Locus Method -- 8. Frequency Response Methods -- 9. Stability in the Frequency Domain -- 10. The Design of Feedback Control Systems -- 11. The Design of State Variable Feedback Systems -- 12. Robust Control Systems -- 13. Digital Control Systems Appendices (Web Resources) -- A. MATLAB Basics -- B. MathScript RT Module Basics -- C. Symbols, Units, and Conversion Factors -- D. Laplace Transform Pairs -- E. An Introduction to Matrix Algebra -- F. Decibel Conversion -- G. Complex Numbers -- H. z-Transform Pairs -- I. Discrete-Time Evaluation of the Time Response -- J. Design Aids.
Includes bibliographical references and index.
Keywords: FEEDBACK CONTROL SYSTEMS